(untitled) (Research, Society and Development, 2021)
Tomato is one of the most demanding agricultural crops in potassium (K), and the correct supply of the nutrient is decisive for the success of the activity. In organic fruit production, potassium fertilization is especially complex. In Brazil, the scenario does not help the organic tomato producer, most certified inputs have low K content and solubility, and, in many cases, low response to fertilization. This study aimed to evaluate the productivity and quality of italian tomato fruits submitted to potassium fertilization with three sources of free use in organic agriculture. The treatments consisted of two certified potassium sulfates (Polivida and Allganic) and an organic residue from the coffee powder industry (coffee pellicle), in doses of 500 and 700 kg ha-1 of K2O, totally at planting or divided into planting plus three coverages. The seedling survival rate, production (number and mass) and quality (rate of hollow and full fruits and total soluble solids) of fruits were evaluated. The results show no statistical difference between treatments for both production and quality (rate of hollow, full and total soluble solids) of the fruits. However, treatments with coffee pellicle required seedling replanting in the first 14 days after transplanting, increasing cultivation costs.